Analysis of bandgap of tellurite glasses doped with Yb3+, Er3+ y Tm3+ - Chacaliaza Ricaldi, José Yitzhak Aarón (2021)
Tellurite glasses have various potential applications in the areas of optoelectronics and photonics, such as laser technology and fiber optics, optical amplifiers, sensors and light converters. These materials are excellent candidates for such applications due to their high solubility for rare earth ions. In the present work, the relationship between the concentration of rare earths in tellurite glasses and its relationship with the optical bandgap and the structural properties of the material was studied.